Parental and peer attachment and its relationship with positive youth development - Mohamed, Nor Hidayah; Hamzah, Siti Raba'ah; Ismail, Ismi Arif; Abu Samah, Bahaman (Human Resource Management Academic Research Society, 2017)
The role of parental and peer attachment in youth development is widely deliberated by scholars in human development. The importance of these two components cannot be denied because they are the closest components in the development of the individual youths. In this article we examined the relationship between parental and peer attachment with youth development using the 5Cs in the Positive Youth Development (PYD) Model. The 5Cs are competence, confidence, connection, character, caring & compassion. A structural equation model was tested on a sample of 677 youths at community colleges in Malaysia ranging in age from 18 to 23 years (M = 19.47, SD = 3.59). This study utilised the self-administered survey questionnaires. The result showed there was a significant relationship between both factors with PYD. Implications of the study showed parental and peer attachment were contributing factors towards positive youth development.